ANALISA KEKUATAN YANG MENDORONG PERTUMBUHAN KEWIRAUSAHAAN MAHASISWA IAIN PURWOKERTO - Sulasih, Sofia (El-Jizya : Jurnal Ekonomi Islam, 2017)
ABSTRACT This research implemented a quantitative research. The data consisted of statistical computation derived from questionnaires collected from the students of IAIN Purwokerto as the samples of this study. This research was entitled as the analysis of the factors that fostered the growth of entrepreneurship among the students at IAIN Purwokerto. The purpose of this study was to analyze and describe the factors that fostered the growth of entrepreneurship among the students at IAIN Purwokerto. The population of this study was the students of IAIN Purwokerto who were considered to be able to represent the population of this research. The number of respondents in this research was 100 respondents. The data analysis method implemented a quantitative analysis by using validity and reliability test, classical assumption test, multiple regression analysis, and t-test. The results of this research showed that the personal strength had the t-value as 1.047 in which it was lower than t-table as 1.661 with a significant level of 0.298 in which it was higher than 0.05. This means that personal strength did not show positive effect that could encourage the growth of entrepreneurship among the students of IAIN Purwokerto. The sociological strengths showed the t-value as 4.743 in which it was higher than t-table of 1.661 with significant level 0.000 in which it was lower 0.05. This means that the sociological strengths had a positive effect to foster the growth of entrepreneurship among the students of IAIN Purwokerto. The social environmental strengths showed that the t-value as 2.175 in which it was higher than t-table as 1.661 with a significant level of 0.032 in which it was lower than 0.05. This means that the social environmental strengths had a positive effect that encouraged the growth of entrepreneurship among the students of IAIN Purwokerto. Keywords: personal strength, sociological strength, social environmental strength, entrepreneurship growth